Campur Kode dalam Podcast Suara Berkelas “Cara Menemukan Bahagia dan Bersyukur Versi Kamu Sendiri Maudi Ayunda" - Gatri Andriani; Deka; Fatmawati (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2026)
Language plays a crucial role as a means of communication in bilingual communities, where the use of two or more languages often gives rise to various linguistic phenomena, one of which is code-mixing. This phenomenon has become increasingly prevalent in digital media, particularly podcasts, which have emerged as a popular communication platform. This study aims to describe the forms of code-mixing and identify the factors contributing to its occurrence in Maudy Ayunda's podcast. A descriptive qualitative method was employed, with the data consisting of utterances containing code-mixing extracted from the podcast. Data were collected through observation, note-taking, and documentation techniques, and analyzed using Suwito's theory of code-mixing and Chaer and Agustina's theory of the factors influencing code-mixing. The findings reveal that the code-mixing used in Maudy Ayunda's podcast encompasses various forms influenced by linguistic, social, and situational factors. These findings provide insights into the practice of code-mixing in digital media and contribute to the advancement of sociolinguistic studies, particularly regarding language use in contemporary communication platforms.